PENGARUH USIA PEMBERIAN MP-ASI DINI DENGAN KEJADIAN STUNTING PADA BALITA 12-23 BULAN DI DESA GEDUNGBOYOUNTUNG - Sholikha, Siti; Hawa Yunarta, Viola Distiar; Muthoharoh, Husnul (Bahasa Indonesia, 2024)
Stunting is a condition that describes a history of malnutrition accompanied by stunted growth due to malnutrition that occurs over a long period of time. Malnutrition occurs when the baby is in the womb and at the beginning of the baby's birth, however, stunting conditions will appear when the baby is 2 years old. This study aims to analyze the effect of giving early MP-ASI on the incidence of stunting in toddlers 12-23 months. This research is an analytical observational study with a cross sectional approach. This research data uses secondary data. The population in this study was 108 toddlers aged 12-23 months in Gedungboyountung Village. Meanwhile, the sample used was 97 who met the inclusion and exclusion criteria, taken using simple random sampling. The results of statistical tests on the influence of the age of first giving MP-ASI and the type of first MP-ASI on stunting show a value of p = 0.073 and p = 0.415, so there is no effect of the age of first giving MP-ASI on the risk of stunting in toddlers aged 12-23 months in Gedungboyoutung Village. The conclusion of this research is that the age at which MP-ASI is given and the type of MP-ASI does not influence the risk of stunting in toddlers aged 12-23 months in Gedungboyoutung Village.